PENGARUH PIMPINAN DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI DALAM PELAKSANAAN E-PROCUREMENT DI KABUPATEN BANYUASIN - M.Kurniawan. DP (Jurnal Ilmiah Ekonomi Global Masa Kini)
The study was carried out to prove that through the development of technology will bring a variety of claims for the organization, to be able to keep up with technology in order to improve the capacity and quality of the organization also needed the support of the leadership in the development of human resources for the betterment of the organization in terms of the local government. The phenomenon of the implementation of government free from corruption, collusion and nepotism makes many government agencies do some procedural changes in its operations. The existence of the spirit to create the procurement of goods and services better, change the system of procurement of goods and services have traditionally been moving towards a system of procurement of goods and services electronically (e-procurement), in the implementation of this system will reduce the interaction between the committee and the providers of goods / services and make the buying process more open and can be easily accessed by the bidders.This study aims to determine the extent of the influence of management support and human resource capacity to employee performance in the implementation of e-procurement in the district Banyuasin. Keywords: Leadership, Human Resource Capacity and Performance